PENINGKATAN PENGETAHUAN ORANG TUA ANAK USIA TAMAN KANAK-KANAK TENTANG PEMENUHAN GIZI DAN PENCEGAHAN STUNTING MELALUI EDUKASI SUPLEMEN MADU LELE (Clarias sp) - Lilik Ariyanti; Atur Semartini (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The Saving Challenge Program was a community service activity conducted by university students participating in the Community Service Program (KKN) in Bahliran Siborna Village, Panei Subdistrict, Simalungun Regency, from August 17 to 28, 2025. This program aimed to foster early financial literacy by cultivating saving habits among children. The target participants included kindergarten and elementary school students. The program was implemented through interactive educational sessions emphasizing the importance of saving, followed by a daily saving challenge conducted over a two-week period using specially prepared piggy banks. The results demonstrated a high level of enthusiasm and active participation among the children. Most participants were able to achieve, and in some cases exceed, the predetermined saving targets. In addition to improving basic financial literacy, the program contributed to the development of discipline, financial independence, and positive money management habits. Overall, the Saving Challenge Program shows strong potential as a community-based financial education model that is both effective and sustainable.